DIGITAL TECHNOLOGY POLICY FOR SMEs: A BIBLIOMETRIC ANALYSIS - Agus Aribowo; Amir Machmud; Anny Nurbasari; Zulkefly Abdul Karim; Asep Ridwan Lubis; Asep Miftahuddin (Sosiohumaniora, 2023)
This study aims to analyze digital technology policies, especially for SMEs publication trends regarding time, author, journal, affiliation, and institution; research areas that are prominent and influential on digital technology policies, especially for SMEs, as well as opportunities and limitations for future researchers to explore. This study uses Scientometrics analysis through bibliometric analysis. Data analysis was carried out in two parts through inductive analysis where the first was bibliometric analysis and in the second part, network mapping. Data were extracted from the Scopus database, in November 2021 during the period 2003-2021. The results of the study show that the highest publications were in 2020 as many as 19 documents; the most relevant source is Telecommunications Policy, the most cited authors are Depaoli, Paolo and the most relevant affiliate is Loughborough University. The results of the study have implications that in the future Digital Technology Policy for SMEs research will focus on studies on Digital Technologies barriers, innovation-diffusion, SME innovation and E-Business.